Coup Culture: The Military and the Failure of Constitutionalism in Fiji - Wilson, Sarah (Victoria University of Wellington Law Review, 2011)
Fiji's Interim Military Government has now been in power for nearly five years. Since that time elections have been promised for 2014, but whether those elections will take place, or how they will be carried out in practice, remains to be seen. This paper is a focus on the checks and balances on the Military Forces in Fiji, and how those could be adapted to restrict military power in the island state.